Acceptability of seasonal influenza vaccines among health care workers in Vietnam in 2017 - Nguyen, Thoa Thi Minh (Vaccine, 2020)
INTRODUCTION: A demonstration project in Vietnam provided 11,000 doses of human seasonal influenza vaccine free of charge to healthcare workers (HCWs) in 4 provinces of Vietnam. Through this project, we conducted an acceptability survey to identify the main reasons that individuals chose to be vaccinated or not to inform and improve future immunization activities. METHODS: We conducted a descriptive cross-sectional survey from May to August 2017 among HCWs at 13 selected health facilities. We employed logistic regression to determine the association between demographic and professional factors, and the decision to receive seasonal influenza vaccine. We performed post-hoc pairwise comparisons among reasons for and against vaccination using Chi square and Fisher’s exact tests (for cell sizes <5). RESULTS: A total of 1,450 HCWs participated in the survey, with a higher proportion of females than males (74% versus 26%). The median age of the participating HCWs was 35 years (median range 25.8 – 44.2). Among those surveyed, 700 (48%) HCWs were vaccinated against seasonal influenza during the first half of 2017. Younger HCWs under 30 and 30–39 years old were less likely to get vaccinated against seasonal influenza than HCWs ≥50 years old (OR=0.5; 95%CI 0.4–0.8 and OR=0.6; 95%CI 0.4–0.8 respectively). Nurses and other employees were more likely to get seasonal influenza vaccination than physicians (OR=1.5; 95%CI 1.0–2.4 and OR=2.0; 95%CI 1.2–3.2 respectively). The most common reason for accepting vaccination was fear of getting influenza (66%) and the most common reason for not getting vaccinated was concern about vaccine side effects (23%). CONCLUSION: Acceptability of seasonal influenza vaccines in this setting varied among HCWs by age group and job category. Interventions to increase acceptance of vaccine among HCWs in this setting where influenza vaccine is being introduced free for the first time should include targeted risk communication on vaccine safety and efficacy.